HUBUNGAN ANTARA KUALITAS TIDUR DAN PRODUKTIVITAS KERJA PADA KARYAWAN USIA PRODUKTIF - Indri Reslinga; Fransisca Chondro (Jurnal Akta Trimedika, 2025)
Work productivity can be defined as the relationship between effort and tangible results in the form of goods and services. According to APO (Asian Productivity Organization) in 2019, Indonesia's worker productivity ranks fifth out of ten ASEAN countries. Sleep quality is a risk factor that can affect productivity. Poor sleep quality can cause complaints such as tired eyes, drowsiness and even falling asleep at work so that it will interfere with work and cause a decrease in employee performance. Previous research shows various results therefore further study to determine the relationship between sleep quality and work productivity is important. This is an observational analytic study with cross sectional design involving 93 employees with consecutive non-random sampling technique. The inclusion criteria in this study were active employees with at least one month of work and aged 20-60 years, able to communicate well and willing to sign informed consent, while the exclusion criteria were employees who took sleeping pills, had a history of diagnosis of psychological disorders, and had a history of diagnosis of diabetes mellitus. Data analysis was performed using the chi-square test on the SPSS version 25 program using a significance level of 0.05. The results showed that the characteristics of the majority of respondents aged 31-40 years (48.4%) and male (50.5%) with significant relationship between sleep quality and work productivity in productive age employees with a p value = 0.002 (p <0.05).